Irish parade murder [compact disc, unabridged] - Meier, Leslie (Meier, Leslie. Lucy Stone mystery., 2021)
Lucy Stone is gearing up for Tinker's Cove's annual St. Patrick's Day celebration, but there's just one wee problem that not even the luck of the Irish can fix--murder!